PENGARUH MODEL PEMBELAJARAN DISCOVERY LEARNING TERHADAP BERPIKIR KRITIS SISWA - Helsya, Rasty; Gimin, Gimin; Primahardani, Indra (Komunitas Manajemen Kompetitif, 2024)
This research is based on problems in the learning process at Taruna Sakti Pekanbaru Middle School, especially class VIII in students becoming less interested in the learning process. The conventional model is also one-way, where the teacher only delivers material using the lecture method so that students tend not to pay attention to the teacher when giving explanations, showing a lack of focus and active involvement in the learning process. Therefore, to improve students' critical thingking, a new learning model is used, namely the discovery learning model. The formulation of the problem in this research is whether there is an influence of the discovery learning model on critical thingking in Civics learning for class VIII students at Taruna Sakti Middle School, Pekanbaru. The populations in this study was class VIII students at Taruna Sakti Middle School pekanbaru with a total of 83 students. The sample in this study consisted of 57 students, who were divided into two class VIII B and class VIII C. The data collection methods used in this research are observation, questionnaires. Data processing using statistical analysis using the t test formula is obtained tcount = 3.012 dan ttable = 2.004, which means that tcount is greater than ttable, thus H0 is rejected and Ha is accepted. So it can be concluded that the discovery learning model affects the critical thingking of students in class VIII SMP Taruna Sakti Pekanbaru by obtaining an average value of 67,8% in the experimental class and the average value of 44,8 % in the control class. Keywords: Discovery Learning Model, Critical Thingking, Civic Education